2018
DOI: 10.47313/pujangga.v3i2.442
|View full text |Cite
|
Sign up to set email alerts
|

Implikatur: Fungsi Tindak Tutur Dalam the Big Bang Theory

Abstract: <p><em>The research basically aims at describing implicature utterances and implicature </em><em>strategy of the speech acts and its types of utterance used in the situation comedy series of The Big Bang Theory seen from the Pragmatics point of view</em><em>. </em><em>The data is analyzed and described qualitatively by examining the correlation of the implicature strategy of the speech acts and its types of utterance. The data of this research is the implicature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The identification of research data involves the use of implicature forms and functions found in the news headlines of Solopos.com newspaper. Furthermore, the classification of implicature functions is based on Searle's theory [31], namely: assertive, directive, commissive, expressive, and declarative. In the study titled "Implicatures in the News on Solopos.com Newspaper," the implicature functions focused on only three functions, and these three functions were found unsuitable as a theory related to the research.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of research data involves the use of implicature forms and functions found in the news headlines of Solopos.com newspaper. Furthermore, the classification of implicature functions is based on Searle's theory [31], namely: assertive, directive, commissive, expressive, and declarative. In the study titled "Implicatures in the News on Solopos.com Newspaper," the implicature functions focused on only three functions, and these three functions were found unsuitable as a theory related to the research.…”
Section: Methodsmentioning
confidence: 99%
“…In data (7) Kinan and Laut are enjoying food at a food stall while discussing why Laut prefers to study in Yogyakarta instead of at UNS (Sebelas Maret University, Solo). Hearing Laut's answer that he wanted to meet and exchange ideas with young people at UGM, Kinan gave advice so that Laut could differentiate between students who have big, bright ideas or those who just speak as they please without any intention or content in it.…”
Section: Advice Directive Speech Actmentioning
confidence: 99%
“…Directive speech acts (DSA) also have various functions that can support an utterance. Searle [7] describes several functions of directive speech. They are: (a) ordering DSA, which is the words stated by the speaker to order the speech partner.…”
Section: Introduction Sectionmentioning
confidence: 99%